2017
DOI: 10.3791/55446
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Termination of Transcription Using BrUTP-strand-specific Transcription Run-on (TRO) Approach

Abstract: This manuscript describes a protocol for detecting transcription termination defect in vivo. The strand-specific TRO protocol using BrUTP described here is a powerful experimental approach for analyzing the transcription termination defect under physiological conditions. Like the traditional TRO assay, it relies on the presence of a transcriptionally active polymerase beyond the 3' end of the gene as an indicator of a transcription termination defect. It overcomes two major problems encountered with the tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…TRO assay was performed essentially as described in [61]. HEM3, BLM10, and SEN1 genes in wild type, sua7-1 and sua7-1 (A) Overexpression of SSU72 in rpb4∆ cells restores the formation of gene loops to wt levels.…”
Section: Tro Assaysmentioning
confidence: 99%
“…TRO assay was performed essentially as described in [61]. HEM3, BLM10, and SEN1 genes in wild type, sua7-1 and sua7-1 (A) Overexpression of SSU72 in rpb4∆ cells restores the formation of gene loops to wt levels.…”
Section: Tro Assaysmentioning
confidence: 99%
“…With the development of halogenated nucleoside triphosphates such as 5-bromouridine-5′-triphosphate (BrUTP) which are detected by specific antibodies, a wide range of possible downstream applications emerged ( Gratzner, 1982 ; Dundr and Raska, 1993 ; Jensen et al, 1993 ; Wansink et al, 1993 ; Chang et al, 2000 ). However, BrUTP is not absorbed well by living cells, and thus it has to be applied on isolated nuclei in so-called run-on assays ( Thompson et al, 1997 ; Dhoondia et al, 2017 ), or introduced into cells via transfection, injection, or electroporation ( Waksmundzka and Debey, 2001 ). Molecules such as 5-bromouridine (BrU), 5-iodouridine (IU), or 5-fluorouridine (FU), on the other hand, are efficiently taken up by living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Since a terminator proximal intron has been shown to affect termination in metazoans, and intron-dependent gene looping involves a terminator-intron interaction as well, we next examined if the presence of an intron in general, and that of the terminator-proximal intron in particular affect termination of transcription. We monitored termination by transcription run-on (TRO) assay as described in Dhoondia et al (2017) for IMD4 gene with the intron inserted at three different positions as shown in Figure 6A . TRO assay detects the presence of transcriptionally active polymerases on a gene as shown in Figure 6B .…”
Section: Resultsmentioning
confidence: 99%
“…The strand-specific “Transcription Run-On” (TRO) assay was performed as described in ( Dhoondia et al, 2017 ). The primers used for making cDNA and PCR are described in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%